Nonalcoholic fatty liver disease progression rates to cirrhosis and progression of cirrhosis to decompensation and mortality: a real world analysis of Medicare data. Issue 11 (5th May 2020) - Loomba, Rohit; Wong, Robert; Fraysse, Jeremy; Shreay, Sanatan; Li, Suying; Harrison, Stephen; Gordon, Stuart C.
Summary: Background: Risk factors and timing associated with disease progression and mortality in nonalcoholic fatty liver disease (NAFLD) are poorly understood. Aims: To evaluate the impact of disease severity, demographics and comorbidities on risk of mortality and time to progression in a large, real‐world cohort of diagnosed NAFLD patients. Methods: Claims data from a 20% Medicare representative sample between 2007 and 2015 were analysed retrospectively. Adults were categorised into disease severity groups: NAFLD/nonalcoholic steatohepatitis (NASH) alone, compensated cirrhosis, decompensated cirrhosis, liver transplant or hepatocellular carcinoma. Cumulative incidence of mortality and disease progression were calculated for each group and multivariate analyses performed adjusting for demographics, comorbidities and disease severity. Results: A total of 10 826 456, patients were assessed and the prevalence of NAFLD was 5.7% (N = 621 253). Among patients with NAFLD, 71.1% had NAFLD/NASH alone and 28.9% had NAFLD cirrhosis. Overall, 85.5% of patients had hypertension, 84.1% dyslipidemia, 68.7% had cardiovascular disease and 55.5% diabetes. The cumulative risk of progression of NAFLD to cirrhosis, and compensated cirrhosis to decompensated cirrhosis was 39% and 45%, respectively, over 8 years of follow‐up. The independent predictors of progression included cardiovascular disease, renal impairment, dyslipidemia and diabetes. The cumulative risk of mortality for NAFLD, NAFLD cirrhosis, decompensated cirrhosis and hepatocellular carcinoma was 12.6%, 31.1%, 51.4% and 76.2%, respectively. Conclusions: The present report (a) demonstrates that NAFLD is grossly underdiagnosed in real‐world clinical settings and (b) provides new evidence on the progression rates of NAFLD and risk factors of mortality across the spectrum of severity of NAFLD and cirrhosis.